An overview of 18F-fluorodeoxyglucose positron emission tomography/computed tomography in giant cell arteritis - Thibault, Thomas; Alberini, Jean-Louis; Billet, Anne-Claire; Greigert, Hélène; Ramon, André; Devilliers, Hervé; Cochet, Alexandre; Bonnotte, Bernard; Samson, Maxime (Frontiers in Medicine, 2024)
PET/CT is an imaging modality that is increasingly being used to diagnose large-vessel vasculitis. In the case of giant cell arteritis, it was first used to demonstrate inflammation of the walls of large arterial trunks such as the aorta and its main branches, showing that aortic involvement is common in this vasculitis and associated with the occurrence of aortic complications such as aneurysms. More recently, with the advent of digital PET/CT, study of the cranial arteries (i.e. temporal, occipital, maxillary and vertebral arteries) has become possible, further increasing the diagnostic interest of this examination for the diagnosis of GCA. Despite these advantages, there are still limitations and questions regarding the use of PET/CT for the diagnosis and especially the follow-up of GCA. The aim of this review is to take stock of currently available data on the use of PET/CT for GCA diagnosis and follow-up.